(untitled) (Bangladesh Pharmaceutical Journal, 2013)
Fexofenadine HCl immediate release tablets were designed to increase the dissolution rate by using superdisintegrants. Different formulations of Fexofenadine HCl were prepared by direct compression method. These formulations were evaluated for hardness, thickness, friability, weight variation, disintegration time, and in vitro dissolution study. The drug release from the formulations were studied according to USP specification (USP paddle method at 50 rpm for 60 minutes) maintaining the temperature to 37°C. Sodium starch glycolate, cross carmellose sodium, crospovidone (kollidon CL), ludiflash and xanthan gum were used in 3%, 6% and 8% concentrations as superdisintegrants. Thus, the ratio of superdisintegrants was changed whereas all the other excipients as well as the active drug (Fexofenadine HCl) remained same in every formulation. Here, 0.001N HCl was used as dissolution medium according to USP and absorbances were determined by using UV spectrophotometer at 217 nm. The F-3 and F-6 formulation prepared by 8% of Sodium starch glycolate and 8% of Cross carmellose sodium showed 99.99% drug release within 30 minutes and 45 minutes, respectively. The disintegration times of F-3 and F-6 formulation were within 9 seconds. The interactions between drug and excipients were characterized by FTIR spectroscopic study. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14483 Bangladesh Pharmaceutical Journal 16(1): 1-9, 2013